Representasi Persahabatan dalam Film Agak Laen (Analisis Semiotika Charles Sander Peirce dalam Film Agak Laen) - Kusmawan, Indra; Kusumawati, Nina; Nurdiansyah, Chepi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Films serve not only as entertainment but also as a medium for conveying social, political, and cultural messages. Through narrative, visual, and semiotic techniques, films have the power to evoke emotional and intellectual responses, encouraging deep reflection on social realities. The film Agak Laen was chosen for this study due to its portrayal of the dynamics of friendship. The purpose of this research is to analyze how friendship is represented in the film using Charles Sander Peirce’s semiotic theory, which includes three core elements: sign, object, and interpretant. This research employs qualitative methods with a semiotic analysis approach. The results reveal that the film Agak Laen conveys messages about the meaning of friendship, as reflected through four components found in each scene: affection in friendship (friendship’s affective), social elements (sociability elements), shared and communal experiences, and the quality of the friendship.